2014
DOI: 10.1080/09540121.2014.896451
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of antiretroviral adherence and viral load among transgender women living with HIV

Abstract: Transgender women are 49 times more likely to become HIV infected than other groups, yet they are drastically underserved by current treatment efforts and report lower rates of treatment adherence then other groups. The objective of this study was to explore correlates of antiretroviral (ART) adherence and viral load among HIV-positive transgender women on ART utilizing a cross-sectional survey of a convenience sample of 59 transgender women. In multivariate models of ART adherence, correlates were age, stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 29 publications
(30 reference statements)
4
49
2
1
Order By: Relevance
“…Given our results that current HT users may report higher rates of HT or ART adherence, our findings support previous data, 29,30 suggesting that gender-affirming healthcare, including clinical integration of HT and ART services, may improve engagement in HIV care for TW.…”
Section: Braun Et Alsupporting
confidence: 81%
See 1 more Smart Citation
“…Given our results that current HT users may report higher rates of HT or ART adherence, our findings support previous data, 29,30 suggesting that gender-affirming healthcare, including clinical integration of HT and ART services, may improve engagement in HIV care for TW.…”
Section: Braun Et Alsupporting
confidence: 81%
“…Considering the recent findings that (1) TW may have suboptimal ART adherence, 28,29 and (2) higher HT adherence and access to other transgender-specific healthcare factors is associated with higher ART adherence, 30 opportunities exist to utilize this synergy to ensure greater participation in HIV care by TW. Given our results that current HT users may report higher rates of HT or ART adherence, our findings support previous data, 29,30 suggesting that gender-affirming healthcare, including clinical integration of HT and ART services, may improve engagement in HIV care for TW.…”
Section: Braun Et Almentioning
confidence: 99%
“…Some barriers to PrEP effectiveness among trans women have already been identified, such as the complex and heterogeneous psychosocial motivations for engaging in risk compensation among trans women (Golub, 2014), as well as many correlates to poor PrEP adherence (Golub, et al, 2013). Particular attention should also be paid to unique barriers that trans women may experience while obtaining access to PrEP, such as gender discrimination, transphobia, and violence, which have been observed to play an important role in reducing acceptability of and access to other HIV testing, preventive and treatment services (Golub & Gamarel, 2013; Golub et al, 2013; Sevelius, Patouhas, Keatley, & Johnson, 2014; Sevelius, Saberi, & Johnson, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, multiple studies support that transgender women living with HIV (TWLWH) were less likely to report higher adherence to anti-retroviral therapy (ART) compared to other adults with HIV (Sevelius, Carrico, & Johnson, 2010; Mizuno, Frazier, Huang & Skarbinski, 2015). In TWLWH, ART adherence has been associated with older age, abstinence from alcohol, positive gender affirmation and adherence to hormones (Sevelius, Saberi, & Johnson, 2014). Similarly, in our previous analysis of adherence and symptom experience among adults living with HIV (Gay et al, 2011), we found that our group of TWLWH reported significantly poorer adherence compared to other adults.…”
Section: Introductionmentioning
confidence: 99%